Pharmacologic inhibition of IL11/STAT3 signaling increases MHC-I expression and T cell infiltration - Wenjun Xiong; Yuehong Chen; Chaoting Zhang; Jin Li; Haipeng Huang; Yu Zhu; Guangxu Deng; Junhong Cheng; Yixiong Lin; Zhimin Shi; Tingyu Mou (Journal of Translational Medicine, 2023)
Abstract Background Recent studies have discovered an emerging role of IL11 in various colitis-associated cancers, suggesting that IL11 mainly promotes tumor cell survival and proliferation in regulating tumorigenesis. Herein we aimed to reveal a novel function of IL-11 through STAT3 signaling in regulating tumor immune evasion. Methods AOM/DSS model in Il11 −/− and Apc min/+/Il11 −/− mice were used to detect tumor growth and CD8+ T infiltration. STAT1/3 phosphorylation and MHC-I, CXCL9, H2-K1 and H2-D1 expression were detected in MC38 cells and intestine organoids treated with/without recombinant IL11 to explore effect of IL11/STAT3 signaling, with IL11 mutein used to competitively inhibit IL11 and rescue inhibited STAT1 activation. Correlation between IL11 and CD8+ T infiltration was analyzed using TIMER2.0 website. IL11 expression and survival prognosis was analyzed in clinical data of patient cohort from Nanfang Hospital. Results IL11 is highly expressed in CRC and indicates unfavorable prognosis. IL11 knockout increased CD8+ T cell infiltration and reduced intestinal and colon formation. Tumors were significantly suppressed while MHC-I and CXCL9 expression for CD8+ T infiltration were remarkably increased in the tumor tissues of Apc min/+/Il11 −/− mice or Il11 −/− mice induced by AOM/DSS. IL11/STAT3 signaling downregulated MHC-I and CXCL9 by inhibiting IFNγ-induced STAT1 phosphorylation. IL11 mutein competitively inhibit IL11 to upregulate CXCL9 and MHC-I in tumor and attenuated tumor growth. Conclusions This study ascribes for a new immunomodulatory role for IL11 during tumor development that is amenable to anti-cytokine based therapy of colon cancer.